If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + 15x = 17x Solving -18 + 15x = 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. -18 + 15x + -17x = 17x + -17x Combine like terms: 15x + -17x = -2x -18 + -2x = 17x + -17x Combine like terms: 17x + -17x = 0 -18 + -2x = 0 Add '18' to each side of the equation. -18 + 18 + -2x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -2x = 0 + 18 -2x = 0 + 18 Combine like terms: 0 + 18 = 18 -2x = 18 Divide each side by '-2'. x = -9 Simplifying x = -9
| x-21=25-3x | | 4x+40=(4x+40)*2 | | -2x-6-3=1 | | 2(6d+3)=18-3(16d-3d) | | -104=-6x-3x+4 | | 10a+5[a-3]=15 | | 3-x+3=5x | | 6-8x=7x-10+11 | | 14-3a+7a=94 | | 4q+4=-2q-8 | | -6(x-1)=14-2x | | 9x-27=9(11-x) | | 6-2x=-12 | | -2x+4(3x+5)=-60 | | 0.3x-0.4=2 | | 7p-5=69+8 | | 5(x+2)=(x+6) | | -8k+k=-14 | | x/4-x/3= | | .5x+5=17 | | 2(x+1)+4=16 | | 5-3(x-7)=26-2x | | 15+2x-3=2x+5 | | 5(4x+9)=9(2x+3) | | 0.5(14x+8)=6x+8 | | -4m-11=-3m-14 | | 6x+9x-21=105-6x | | -2k-5=-k+3 | | m-9m-8m-5= | | 1+x=x-5 | | 2x+6x+8=36 | | -3(m-8)=3 |